2016
DOI: 10.1093/hmg/ddw373
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia-associated methylomic variation: molecular signatures of disease and polygenic risk burden across multiple brain regions

Abstract: Genetic association studies provide evidence for a substantial polygenic component to schizophrenia, although the neurobiological mechanisms underlying the disorder remain largely undefined. Building on recent studies supporting a role for developmentally regulated epigenetic variation in the molecular aetiology of schizophrenia, this study aimed to identify epigenetic variation associated with both a diagnosis of schizophrenia and elevated polygenic risk burden for the disease across multiple brain regions. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 68 publications
(84 reference statements)
12
66
0
Order By: Relevance
“…These data are consistent with another recently published study that investigated schizophrenia-associated DNA methylation changes across four distinct regions of the human brain in homogenized whole cortex, accounting for estimates of neuronal/glial proportions in each sample [20]. The prior study found multiple DMPositions and DMRegions between schizophrenia and control subjects, and while many were shared across brain regions, the majority of these changes were significant in only a subset of regions, with the cerebellum being the most distinct region assayed.…”
Section: Discussionsupporting
confidence: 91%
“…These data are consistent with another recently published study that investigated schizophrenia-associated DNA methylation changes across four distinct regions of the human brain in homogenized whole cortex, accounting for estimates of neuronal/glial proportions in each sample [20]. The prior study found multiple DMPositions and DMRegions between schizophrenia and control subjects, and while many were shared across brain regions, the majority of these changes were significant in only a subset of regions, with the cerebellum being the most distinct region assayed.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies that investigated DNAm aging in SCZ did not observe significant differential aging [27][28][29][30][31] , highlighting that sample size and/or explicit modeling of age-and sexdependent effects are crucial factors when investigating aging in SCZ. Our findings also demonstrate that analyzing these clocks simultaneously can reveal new insights that may otherwise be missed.…”
Section: Discussionmentioning
confidence: 86%
“…While different aging biomarkers have been studied, there is no clear demonstration of altered aging in SCZ 11 . More specifically, DNAm age predictors have found limited to no evidence for altered epigenetic aging in either brain or blood [27][28][29][30][31] . These studies, however, (i) consisted of small sample sizes and thus limiting the ability to detect a biological signal, (ii) used a single epigenetic clock that may have not been most informative for aging studies of psychiatric disorders, and (iii) did not consider aging differences across the life-span of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the work toward epigenetically characterizing the schizophrenia epigenome has involved measuring direct DNA methylation through bisulphite sequencing and similar methods. For example, a recent study (41 cases, 46 controls) across 4 brain regions found many genome regions that displayed differentially methylated DNA [28], while a larger study (689 cases, 645 controls) using blood samples similarly identified many differentially methylated loci [29]. Other studies support the importance of DNA cytosine methylation in schizophrenia [30-32].…”
Section: Mechanisms Of Epigenetic Regulationmentioning
confidence: 99%